(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Grains marketed under open and poorly controlled storage conditions are highly susceptible to fungal colonization and subsequent aflatoxin contamination, with significant implications for food safety, public health, and economic valuation. This study quantitatively assessed aflatoxin contamination and associated mycobiota in three staple cereals—maize, millet, and sorghum—sourced from Kawo and Kasuwar Bacci markets in Kaduna between April and July 2025. Representative samples (300 g per grain type) were randomly procured from multiple vendors, aseptically packaged in sterile paper envelopes, and transported for laboratory analysis at the National Agency for Food and Drug Administration and Control (NAFDAC) facility. Quantification of total aflatoxins was conducted using a validated enzyme-linked immunosorbent assay (ELISA) protocol, while fungal isolation and enumeration were performed via standard culture-based techniques following surface sterilization. Microbiological analysis revealed that millet samples from Kawo market exhibited the highest fungal burden (3.0 × 10⁵ cfu/g), followed by sorghum (2.0 × 10⁵ cfu/g) and maize (1.2 × 10⁵ cfu/g). Similarly, at Kasuwar Bacci, millet recorded the highest load (1.7 × 10⁵ cfu/g), with maize (1.4 × 10⁵ cfu/g) and sorghum (1.2 × 10⁵ cfu/g) showing comparatively lower counts. Identified fungal taxa included Aspergillus flavus, Aspergillus niger, Penicillium spp., and Mucor spp., all of which are known for their toxigenic potential under favorable conditions. Total aflatoxin concentrations ranged from 2.418 to 2.676 µg/kg, with the maximum value observed in maize samples from Kasuwar Bacci market. Despite detectable fungal contamination, the relatively low aflatoxin levels indicate compliance with established permissible limits, suggesting that the grains remain within acceptable safety thresholds for human consumption.